A new paradigm to govern mobility, risk and uncertainty, the categories of contemporary life - Cocozza, Antonio (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
This essay presents an analysis of the structural and cultural characteristics of postmodern society s new capitalism, underscoring the fact that uncertainty, flexibility, mobility and risk are the categories of contemporary life, with which we need to interact constantly. It is necessary to govern uncertainty by activating a new logic of widespread accountability and empowerment of people aimed at creating value for all stakeholders, through the sharing of objectives, development plans and the joint design of technologies, structures and processes. This is a perspective which places the person at the centre of strategic action, relaunches a New Humanism, invests in the cultural dimension, enhances that of value with a view to surpassing the utilitarian and technocentric paradigm while asserting a new anthropocentric vision.